Manajemen Pemberdayaan Masyarakat Berbasis POAC: Kajian Teoritis dan Praktis dalam Membangun Tata Kelola Pemberdayaan Berkelanjutan - Mardan Mahmuda; Romi Altavia (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2026)
Community empowerment is a development approach that positions communities as the primary actors in social, economic, and institutional transformation. Although various participatory-based empowerment programs have been implemented, their sustainability continues to face challenges related to governance, institutional coordination, resource management, and evaluation. These conditions highlight the importance of a management approach that systematically integrates planning, organizing, implementation, and control. This article aims to analyze the POAC management functions (Planning, Organizing, Actuating, and Controlling) as a conceptual framework for community empowerment through a literature review of scholarly publications addressing management concepts, community empowerment, and the management of local empowerment programs. The review indicates that Planning ensures programs are aligned with community needs; Organizing strengthens institutional structures and clarifies the distribution of roles; Actuating enhances community participation through facilitation and capacity building; whereas Controlling ensures program sustainability through monitoring and evaluation. The findings conclude that POAC provides a comprehensive management framework that integrates organizational governance with the principles of community participation and self-reliance.